Force Sensors: A Highly Sensitive Force Sensor with Fast Response Based on Interlocked Arrays of Indium Tin Oxide Nanosprings toward Human Tactile Perception (Adv. Funct. Mater. 42/2018). (15th October 2018) - Chun, Sungwoo; Choi, Il Yong; Son, Wonkyeong; Bae, Gi Yoon; Lee, Eun Jae; Kwon, Hyunah; Jung, Jaimyun; Kim, Hyoung Seop; Kim, Jong Kyu; Park, Wanjun
Abstract : In article number1804132, Jong Kyu Kim, Wanjun Park, and co‐workers describe a highly sensitive force sensor based on interlocked arrays of vertically aligned rigid indium tin oxide (ITO) nanosprings. Sub‐millisecond response times to both static and dynamic pressures are achieved. Surface texture recognition by rubbing the sensor combined with a finger print structure can classify eight fabrics with 99.8% accuracy, comparable to human tactile perception.